Advanced Electrode Materials Comprising of Structure‐Engineered Quantum Dots for High‐Performance Asymmetric Micro‐Supercapacitors. Issue 8 (29th January 2020) - Liu, Wenwen; Zhang, Maiwen; Li, Matthew; Li, Brenda; Zhang, Wenyao; Li, Gaoran; Xiao, Meiling; Zhu, Jianbing; Yu, Aiping; Chen, Zhongwei
Abstract: Micro‐supercapacitors (MSCs) as a new class of energy storage devices have attracted great attention due to their unique merits. However, the narrow operating voltage, slow frequency response, and relatively low energy density of MSCs are still insufficient. Therefore, an effective strategy to improve their electrochemical performance by innovating upon the design from various aspects remains a huge challenge. Here, surface and structural engineering by downsizing to quantum dot scale, doping heteroatoms, creating more structural defects, and introducing rich functional groups to two dimensional (2D) materials is employed to tailor their physicochemical properties. The resulting nitrogen‐doped graphene quantum dots (N‐GQDs) and molybdenum disulfide quantum dots (MoS2 ‐QDs) show outstanding electrochemical performance as negative and positive electrode materials, respectively. Importantly, the obtained N‐GQDs//MoS2 ‐QDs asymmetric MSCs device exhibits a large operating voltage up to 1.5 V (far exceeding that of most reported MSCs), an ultrafast frequency response (with a short time constant of 0.087 ms), a high energy density of 0.55 mWh cm −3, and long‐term cycling stability. This work not only provides a novel concept for the design of MSCs with enhanced performance but also may have broad application in other energy storage and conversion devices based on QDs materials. Abstract : A novel asymmetric micro‐supercapacitor (MSC) is designed and constructed with capacitor‐type nitrogen‐doped graphene quantum dots as the negative electrode and battery‐type molybdenum disulfide quantum dots as the positive electrode. The obtained MSCs display outstanding electrochemical performance compared to other reported MSCs, including a high energy density, an excellent rate capability, a fast frequency response capability, and long‐term cycling stability.